Implementasi Program UPSUS PAJALE (Upaya Khusus Padi Jagung Kedelai) dalam Rangka Swasembada dan Swasembada Berkelanjutan) - Shafiani, Fanni (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
Agriculture is an important sector for development in Indonesia, most of the population of Indonesia earns a living in this sector as well as the main support of the national economy, How it implementation UPSUS PAJALE program in Sumbawa Regency?. The research method used is a qualitative method with a Grindle implementation model (1980). This study resulted in the finding that the implementation of the UPSUS PAJALE program was easy to implement in Sumbawa Regency because of the findings of non-compliance with SRI (System Rice Intensification) activities due to the limitations of farmers' ability to absorb innovation technology and the gratification of CPCL determination. Theres no attraction between government, society and the private sector, interests are homogeneous so that implementation is easy to implement. This research can be useful as an input to the relevant agencies to plan the next program to be more targeted.